Edukasi Ekonomi Syariah bagi Mahasiswa dan Organisasi Kepemudaan di Kabupaten Lombok Barat - Mashur, Mashur; Yakubi, Muh; Riswandi, Dedi (Jurnal Pemberdayaan Ekonomi, 2024)
Purpose: The aim of this community service activity is, among other things, as a form of education for students and youth as part of the millennial generation by providing knowledge and understanding of Sharia economics and Sharia economic literacy. Apart from that, it can be a stimulus for the attitudes of students and youth towards Sharia economic development trends. Methodology/approach: The form of implementation of this Sharia economic education activity is socialization using lecture and discussion methods to explain material regarding Sharia economics to participants, followed by a question and answer/discussion session between the presenter and service participants. Conclusion: The community service activity program (PKM) through Sharia economic education was implemented well. In conclusion, educational participants have an understanding of the basic concepts of Sharia economics. After participants received material regarding Sharia economics and Sharia economic literacy, they showed increased understanding. Participants had high enthusiasm and responses to the service activities. They hope that there will be discussions regarding Sharia economics more broadly to enrich scientific knowledge. Results/findings: The aim of the service activity was for discussion participants to gain new knowledge regarding the importance of Sharia economics. Students and young people realize that, in fact, Islamic economics is a science that is not only concerned with worldly life but also the life of the afterlife. Limitations: This study focuses on education by attempting to provide an understanding of the fundamentals of the Sharia economy. Contribution: This program serves as a reference for other academics to provide basic understanding (education) to students and youth in the West Lombok district.